2019
DOI: 10.1111/jocn.14797
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and outcomes of non‐vitamin K antagonist oral anticoagulants versus warfarin in patients with non‐valvular atrial fibrillation

Abstract: Aims and objectives To compare persistence and outcomes of non‐vitamin K antagonist oral anticoagulants (NOACs) versus warfarin in Chinese patients with non‐valvular atrial fibrillation (AF). Background Given the unpredictable warfarin response and the costliness of NOACs, more research is needed to clarify which drug enjoys better persistence and outcomes, helping to provide personalised care for patients. Design A prospective cohort study. Methods Chinese patients taking NOACs or warfarin from March 2016–Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
2
15
1
3
Order By: Relevance
“…Compared with warfarin, NOACs are more convenient to use, including advantages such as fixed dose regimens, no requirement for frequent blood monitoring, no food and drug restrictions and less risk of bleeding 26 27. In the current study, we found that there was a substantially increased use of NOACs in Chinese patients during the past few years.…”
Section: Discussionmentioning
confidence: 53%
“…Compared with warfarin, NOACs are more convenient to use, including advantages such as fixed dose regimens, no requirement for frequent blood monitoring, no food and drug restrictions and less risk of bleeding 26 27. In the current study, we found that there was a substantially increased use of NOACs in Chinese patients during the past few years.…”
Section: Discussionmentioning
confidence: 53%
“…Wu et al compared persistence and outcomes of non-vitamin K antagonist oral anticoagulants (NOACs) to warfarin. Patients on NOACs were seen to have worse persistence at 3, 6, and 12 months than those on warfarin; the main reasons for anticoagulant discontinuation cited were related to patient preference such as adverse bleeding events and costs (33).…”
Section: Resultsmentioning
confidence: 99%
“…In the study on atrial fibrillation by Wu et al, persistence to therapy with anticoagulants was strongly influenced by costs, as well as with adverse events to treatment (33). Indeed, patients prescribed NOACs had worse persistence than those given warfarin and the study was carried out in China where, as noted by the authors, NOACs are approximately 80 times more expensive than warfarin, which influences not only preference, but the ability to acquire the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The initial literature search identified 3,359 potentially eligible citations. After primary screening, 150 articles were eligible for full-text review and there were 35 studies 7 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 including 2,356,201 patients that met the inclusion criteria and presented relevant data regarding major bleeding and clinically relevant bleeding ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%